Associations among elements in freshwater mussel shells (Unionidae) and their relation to morphology and life history. (4th August 2021) - Hopper, Garrett W.; Dickinson, Gabriella K.; Atkinson, Carla L.
Abstract: Biogeochemical ecology of organisms typically focuses on C, N, and P despite c . 25 elements needed for organismal function. Embracing novel suites of elements in biomass is a first step in linking elements to organismal and ecological functions, improving our ability to predict how species interact with their environment. This research area has been fruitful for terrestrial plant ecologists, yet few studies have considered animal ecology within a framework encompassing elements beyond C, N, and P. Freshwater mussels (Unionidae) are highly endangered filter‐feeding bivalves that can be important to ecosystem function. Interspecific trait variation influences soft tissue elemental composition that has been linked to ecosystem biogeochemical cycling using traditional C:N:P stoichiometric approaches. However, whether interspecific trait variation influences shell elemental composition is not well studied, especially for elements other than C, N, and P. We quantified B, C, Ca, Cu, Fe, K, Mg, Mn, N, P, and Zn and constructed isometric log‐ratios (nutrient balances) for shells of seven species comprising diverse morphologies and two life history strategies to test whether shell elemental composition is influenced by these biological traits. Additionally, we evaluated whether the growth rate hypothesis applies to shell P concentration and elements associated with P in nutrient balances. Bulk and trace elemental composition varied taxonomically and with biological traits. Nutrient balances for [C | P] and [C, Ca | P] were influenced by life history strategy. Shell P composition was negatively related to growth rates. Coincidentally, [C | P] and [C, Ca | P] were greater in the species with the highest growth rate ( Lampsilis ornata ), suggesting greater concentrations of C and Ca relative to P in shells of faster growing mussels. We hypothesise this observed pattern results from greater P allocation to soft tissue in fast growing mussels compared to slow growing mussels studied previously, but explicit tests of this hypothesis in a strict stoichiometric framework are needed. Overall, we demonstrate how quantifying elements beyond C, N, and P, may be useful in uncovering elemental diversity associated with trade‐offs in elemental allocation among biological traits. Whether such elemental diversity correlates to evolutionary history or contributes to the biogeochemical template of freshwater habitats remains to be seen but should be explored.